State of the nation : South Africa, 2005-2006 - Buhlungu, Sakhela S (Cape Town, South Africa: HSRC Press, 2006)
Summary: State of the Nation: South Africa 2007 offers 22 diverse angles on contemporary South Africa in one compelling and comprehensive collection. The politics section focuses on the outcome of the 2006 local government elections and issues of service delivery. The economy section examines the rapidly growing social welfare net, the state of our public health systems, and the topics of water and the environment, heritage and tourism. Violence against women, prison reform, the plight of South Africa's former guerrilla fighters, transformation in South African rugby and the post-apartheid role of the church all come under the spotlight in the society section. The volume concludes with a look at trends in the continuing involvement of South African business on the African continent, South Africa's part in the complex search for peace and stability in the Democratic Republic of Congo, and the life of the vast Zimbabwean exile community in South Africa.
"In the South African context, the fourth edition of 'State of the nation' continues the tradition ..."--Page xiii
Includes bibliographical references and index.
Adult
Keywords: South Africa